Attitudinal and demographic predictors of measles-mumps-rubella vaccine (MMR) uptake during the UK catch-up campaign 2008-09: cross-sectional survey - Brown,K; Fraser,G; Ramsay,M; Shanley,R; Cowley,N; van,Wijgerden J; Toff,P; Falconer,M; Hudson,M; Green,J; Kroll,JS; Vincent,C; et al. (PLOS One, 2011)
Background and ObjectiveContinued suboptimal measles-mumps-rubella (MMR) vaccine uptake has re-established measles epidemic risk, prompting a UK catch-up campaign in 2008–09 for children who missed MMR doses at scheduled age. Predictors of vaccine uptake during catch-ups are poorly understood, however evidence from routine schedule uptake suggests demographics and attitudes may be central. This work explored this hypothesis using a robust evidence-based measure.DesignCross-sectional self-administered questionnaire with objective behavioural outcome.Setting and Participants365 UK parents, whose children were aged 5–18 years and had received <2 MMR doses before the 2008–09 UK catch-up started.Main Outcome MeasuresParents' attitudes and demographics, parent-reported receipt of invitation to receive catch-up MMR dose(s), and catch-up MMR uptake according to child's medical record (receipt of MMR doses during year 1 of the catch-up).ResultsPerceived social desirability/benefit of MMR uptake (OR=1.76, 95% CI=1.09–2.87) and younger child age (OR=0.78, 95% CI=0.68–0.89) were the only independent predictors of catch-up MMR uptake in the sample overall. Uptake predictors differed by whether the child had received 0 MMR doses or 1 MMR dose before the catch-up. Receipt of catch-up invitation predicted uptake only in the 0 dose group (OR=3.45, 95% CI=1.18–10.05), whilst perceived social desirability/benefit of MMR uptake predicted uptake only in the 1 dose group (OR=9.61, 95% CI=2.57–35.97). Attitudes and demographics explained only 28% of MMR uptake in the 0 dose group compared with 61% in the 1 dose group.ConclusionsCatch-up MMR invitations may effectively move children from 0 to 1 MMR doses (unimmunised to partially immunised), whilst attitudinal interventions highlighting social benefits of MMR may effectively move children from 1 to 2 MMR doses (partially to fully immunised). Older children may be best targeted th